The effectiveness of design relations in the implementation of mural paintings for the facade of the Departments of Family Education and Art Education (The Peerian Journal, 2022)
The current study, which formed its problem based on the question, what is the effectiveness of the design relations in the implementation of the mural panel of the Department of Family Education and Artistic Professions, and the goal of the research included (recognizing the effectiveness of the design relations in implementing the two panels in the family education and art education departments) As for the second chapter, it consists of three sections; In the first topic, the concept of design relations in mural art, the second topic, the design relations, and the third, the nature of mural art, The third chapter also included the research procedures represented by analyzing the two artworks according to the design relations to determine the extent of the effectiveness of these relations. and we came out with the results that answered the question about the research problem, which showed the effectiveness of the design relations in the mural painting and the two works came out as two building units. In its fourth chapter, the researcher also suggested that a study similar to the current study should be conducted, except that it discusses the role of mural art in decorating university yards. The researcher recommended the necessity of making mural arts within the plans of modern buildings because of their distinctive role, and the research ends with the index of sources and appendices.